2020
DOI: 10.3892/mmr.2020.11310
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR‑193a‑3p via targeting cyclin D1 in thyroid cancer

Abstract: Thyroid cancer (Tc) is a frequently occurring malignant tumor with a rising steadily incidence. microrna (mirna/mir)-193a-3p is an mirna that is associated with tumors, playing a crucial role in the genesis and progression of various cancers. However, the expression levels of mir-193a-3p and its molecular mechanisms in Tc remain to be elucidated. The present study aimed to probe the expression of miR-193a-3p and its clinical significance in TC, including its underlying molecular mechanisms. Microarray and rna … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 89 publications
(92 reference statements)
1
5
0
2
Order By: Relevance
“…Next, we investigated the protein expression changes to evaluate the molecular mechanisms involved in the induction of apoptosis. We first examined known direct targets of miR‐193a‐3p including KRAS, 29,34‐37 Mcl1, 38,39 Cyclin D1, 40‐44 CDK4 40 and CDK6, 40 and cleaved PARP, 39 an indirectly dysregulated protein by miR‐193a‐3p expression in various cancers. As shown in Figure 2D, miR‐193a‐3p overexpression reduced the protein expressions of KRAS, Mcl1, Cyclin D1, and CDK6 and increased the protein expression of cleaved PARP, compared with NC‐mimic overexpression in LIM1215 and RKO cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we investigated the protein expression changes to evaluate the molecular mechanisms involved in the induction of apoptosis. We first examined known direct targets of miR‐193a‐3p including KRAS, 29,34‐37 Mcl1, 38,39 Cyclin D1, 40‐44 CDK4 40 and CDK6, 40 and cleaved PARP, 39 an indirectly dysregulated protein by miR‐193a‐3p expression in various cancers. As shown in Figure 2D, miR‐193a‐3p overexpression reduced the protein expressions of KRAS, Mcl1, Cyclin D1, and CDK6 and increased the protein expression of cleaved PARP, compared with NC‐mimic overexpression in LIM1215 and RKO cells.…”
Section: Resultsmentioning
confidence: 99%
“…The results suggested that ATF2 and MYC are indirectly regulated by miR-193a-3p. Collectively, the tumor-suppressive function of miR-193a-3p is likely attributable to the regulation of several oncogenic pathways through indirect modulation of the expressions of ATF2 and MYC, in addition to that of known direct targets such as KRAS, 29,[34][35][36][37] Mcl1, 38,39 and Cyclin D1 [40][41][42][43][44] (Figure 4E).…”
Section: Identification and Validation Of Novel Target Candidates Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…В исследовании X. Li и соавт. была изучена экспрессия miRNA-193a-3p на материале 510 образцов РЩЖ и 59 фрагментов здоровой ткани ЩЖ [54,55]. Результаты показали, что экспрессия miRNA-193a-3p в клетках РЩЖ была значительно ниже, чем в здоровых клетках (p <0,001).…”
Section: микрорнк ассоциированные с дифференцированными формами рака щитовидной железыunclassified
“…Снижение miRNA-193a-3p также было достоверно связано с возрастом, полом и наличием метастазов (p = 0,020; 0,044 и 0,048 соответственно). Биоинформационный анализ данных показал, что низкая экспрессия miRNA-193a-3p может увеличивать экспрессию циклидина D1, который, в свою очередь, активирует пролиферацию и миграцию опухолевых клеток [55].…”
Section: микрорнк ассоциированные с дифференцированными формами рака щитовидной железыunclassified